2018
DOI: 10.13057/biodiv/d190505
|View full text |Cite
|
Sign up to set email alerts
|

Carbon storage variability in seagrass meadows of Marine Poton Bako, East Lombok, West Nusa Tenggara, Indonesia

Abstract: Rahman FA, Qayim I, Wardiatno Y. 2018. Carbon storage variability in seagrass meadows of Marine Poton Bako, EastLombok, West Nusa Tenggara, Indonesia. Biodiversitas 19: 1626-1631. The increase of atmospheric CO2 concentration in the lastdecades leads to global warming, having an adverse effect on the environment condition on the Earth. One of the natural mechanism asan effort to reduce the impact of global warming is carbon absorption and storage through photosynthesis mechanism of seagrassvegetation. Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
0
5
1
12
Order By: Relevance
“…The important value index is one way of calculating the level of mastery of a research object which can be in the form of plants (Rahman et al, 2018). The index of a forest vegetation is highly dependent on habitat conditions which can be influenced by environmental factors so that certain types that can survive, grow and develop well can be seen from the Important Value Index of the types of field observations and data analysis (Rahman et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The important value index is one way of calculating the level of mastery of a research object which can be in the form of plants (Rahman et al, 2018). The index of a forest vegetation is highly dependent on habitat conditions which can be influenced by environmental factors so that certain types that can survive, grow and develop well can be seen from the Important Value Index of the types of field observations and data analysis (Rahman et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 4 Average carbon of below-ground and above-ground of seagrass at Samuh and Sanur sites A similar study throughout Indonesia has found that E. acoroides has been found to have higher quantities of biomass compared to other species of seagrass, which has been argued due to their larger size [47], [48], [49]. The larger morphological size of E. acoroides can accumulate more carbon, 40% of its total biomass [50].…”
Section: B Plant Biomass and Carbon Storagementioning
confidence: 88%
“…Tingkat keanekaragaman dihitung dengan menggunakan indeks keanekaragaman (H') Shanon-Wiener yang menunjukan bahwa keanekaragaman lamun di Perairan Selatan Lombok Timur tergolong kategori sedang (Magurran, 1988). Nilai keanekaragaman dari penelitian ini lebih tinggi jika dibandingkan rata-rata nilai keanekaragaman di Perairan Gili Asahan, Kabupaten Lombok Barat, yaitu 1,27 dengan nilai dominansi 0,34 (Rahman, et al, 2018). Keanekaragaman jenis suatu komunitas dapat dikatakan tinggi apabila komunitas tersebut tersusun dari banyak spesies dengan kelimpahan tiap spesies merata.…”
Section: Indeks Keanekaragaman Keseragaman Dan Dominansiunclassified
“…Salah satunya ekositem lamun di pesisir Lombok Timur. Studi tentang hal ini menunjukkan bahwa pada areal seluas 56.65 ha pada padang lamun di Poton Bakau Lombok Timur adalah 249.27 ton C/ha (Rahman et al, 2018). Namun demikian, penelitian tentang potensi kandungan karbon masih terbatas.…”
unclassified